Synthesis and Electrochemical Characterizations of 7-Ferrocenycarbonyloxy-1-heptanethiol on Gold Substrates - Rahman, M. M.; Jeon, I. C.; Oh, K. J. (Journal of Scientific Research, 2009)
The 7-ferrocenycarbonyloxy-1-heptanethiol (FcCO2C7SH) is synthesized using ferrocene carboxylic acid, 1,6-fibromohexane, and NaS, which is confirmed and separated by FT-IR, 1H NMR, and column chromatography. The basic redox (interfacial) properties are also studied of the self-assembled monolayers (SAMs) formed with this synthesized compound on polycrystalline gold electrode by Electrochemical Quartz Crystal Microbalance (EQCM). The FcCO2C7SH on gold acts as a barrier for the electron transfer between the gold electrode and HClO4 in solutions and as a mediator for the reduction of Fe3+ in solution. The frequency change (interfacial mass change) on the gold electrode surface is observed during the redox of ferrocenyl groups. Keywords: 7-Ferrocenycarbonyloxy-1-heptanethiol; Self-Assembled Monolayers; EQCM; Peak current; Modified gold electrode. © 2009 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. DOI: 10.3329/jsr.v1i2.1746